Workshop: Stunting Prevention Effort in Sidoraharjo Village, Kedamean District, Gresik Regency - Budhi Setianto; Siti Nur Hasina; Difran Nobel Bistara; Agus Aan Adriansyah; Edza Aria Wikurendra; Akas Yekti Pulih Asih; Abdul Hakim Fasya; Dwi Handayani; Aditya Rizky Alfaridzi; Novianti Fatimahtus Zahro; ewi Sinta Nuriatul Imamate (Journal of Health Community Service, 2024)
Stunting is a condition in which children fail to grow, both physically and mentally Reported from Jawa Pos news on July 23, 2022, information obtained by Jawa Pos, NEW data from the Gresik Regency Health Office, until July 2021, there were 5,288 stunting toddlers. This figure comes from the number of children who were weighed and measured as many as 80,663 toddlers. So KKN activities from Group 18 of Sidoraharjo Village held socialization of stunting prevention activities aimed at residents of Sidoraharjo village. The purpose of this activity is to provide knowledge related to stunting prevention. The method used is holding a workshop involving residents of Sidoraharjo, as well as making brochures and posters so that people are more aware of the importance of stunting prevention. The satisfaction of the workshop participants was 89.3% and there was an increase in knowledge of 16.6%. From this activity, it was concluded that this workshop was very beneficial to the participants. The presentation in simple language and followed by a discussion made the participants happy and increased awareness together to prevent stunting.